Hypotensive and Hepatoprotective Properties of the Polysaccharide-Stabilized Foaming Composition Containing Hydrolysate of Whey Proteins - Kruchinin, Alexandr G. (Nutrients, 2021)
Whey protein hydrolysates (WPHs) are one of the most promising sources of biofunctional peptides with such beneficial properties as antioxidant, antihypertensive, anti-inflammatory and others. WPHs also could be used as foaming agents for aerated products (e.g., milk shake type drinks). However, WPH alone has a bitter taste and foamed WPH should be stabilized by additional ingredients. Here, we present a composition including WPH and three polysaccharides—pumpkin pectin, sodium alginate and ι-carrageenan—used as foam stabilizers. Polysaccharide content was selected according to foaming, organoleptic antioxidant and angiotensin-I-converting enzyme inhibitory characteristics of the resulted composition. Further, the hypotensive, antioxidant and hepatoprotective properties of the composition were proved by in vivo tests performed in spontaneously hypertensive rats and Wistar rats with CCl(4)-induced hepatic injury.